Pseudomonas aeruginosa carriage and associated risk factors in healthy individuals and patients from Rotterdam, Rome, and Jakarta - Anneloes van Veen; Selvi N. Shahab; Amber Rijfkogel; Margreet C. Vos; Yulia Rosa Saharman; Anis Karuniawati; Silvia Zelli; Desy De Lorenzis; Giulia Menchinelli; Giulia De Angelis; Maurizio Sanguinetti; Anne F. Voor in ’t holt; et al. (Scientific Reports)
Abstract Pseudomonas aeruginosa may colonize humans, however, epidemiological data are scarce. Here, we determined overall and body site-specific carriage rates and associated risk factors among healthy individuals and newly admitted patients in three major cities. This cross-sectional study was conducted in Rotterdam (The Netherlands), Rome (Italy), and Jakarta (Indonesia) between 2022–2024. Adult healthy individuals and newly admitted patients were asked to provide throat, navel, and rectal/perianal swabs, and to complete a questionnaire. Univariable and multivariable analyses were performed to determine factors associated with P. aeruginosa carriage. Carriage rates differed significantly between cities (p < 0.001), and were lowest in Rome (healthy individuals 4.8%; patients 6.5%), followed by Rotterdam (healthy individuals 12.0%; patients 12.7%), and Jakarta (healthy individuals 28.6%; patients 24.0%). In carriers from Rotterdam, P. aeruginosa was most often detected in perianal swabs, while mostly in throat swabs among carriers from Rome and Jakarta. P. aeruginosa carriage had a seasonal association in patients from Rotterdam (p = 0.014) and Jakarta (p = 0.020). Among patients from Jakarta, female sex (aOR 1.98, 95% CI 1.02–3.84; p = 0.045) was associated with P. aeruginosa carriage. Overall, P. aeruginosa carriage rates and colonized body sites differ between cities and are likely associated with climate differences. Our findings warrant setting-specific adaptations of screening strategies and surveillance programs.